Pengaruh Sistem Zipper Dalam Pemilu 2024 - Mardiah, Adinda Rabiki; Wijayanti, Septi (Legislatif, 2023)
Women's representation in parliament has a very important role to convey the aspirations of society in general and women in particular. After the Constitutional Court Decision No. 22-24 / PUU-VI / 2008 there was a new regulation regarding the mandatory representation of women as much as 30% in parliament. However, until the 2019 elections were held, women's representation in parliament had not reached 30%. One of which reason women representation still under 30% is zipper system used in electoral system. Zipper system is an election system by placing male and female candidates intermittently. Indonesia applied a semi-pure zipper system with a proportion of 3: 1 and not a 1: 2 system. Therefore, the purpose of this study is to determine the opportunity of implementing zipper system in the upcoming 2024 election. This research is a normative juridical research using secondary data materials which are divided into three groups, namely primary legal materials in the form of laws and regulations, secondary legal materials in the form of articles and books that explain primary legal materials which are then presented qualitatively. In conclusion, looking at the pattern of Indonesian voters towards female candidates, the implementation of the zipper system with the 3:1 scheme applied in Indonesia can only increase the number of women's candidacy, not the number of electability. The dominance of young voters in the 2024 election can encourage women's electability with changes to the pure zipper system and political education about the importance of women's representation.